Micelle‐enhanced spectrofluorimetric method for quantification of entacapone in tablets and human plasma. (5th December 2016) - Belal, F.; Ibrahim, F.; Sheribah, Z. A.; Alaa, H.
Abstract: In this paper, a simple and highly sensitive spectrofluorimetric method was developed and validated for the determination of entacapone (ETC). The proposed method is based on forming a highly fluorescent product through the reduction of ETC with Zn/HCl. The produced fluorophore exhibits strong fluorescence at λem 345 nm after excitation at λex 240 nm. The use of fluorescence enhancers such as Tween‐80 and carboxy methyl cellulose (CMC) greatly enhanced the fluorescence of the produced fluorophore by 150% and 200%, respectively. Calibration curves showed good linear regression (r2 > 0.9998) within test ranges of 0.05–2.0 and 0.02–1.80 μg mL −1 with lower detection limits of 1.27 × 10 −2 and 4.8 × 10 −3 μg mL −1 and lower quantification limits of 4.21 × 10 −2 and 1.61 × 10 −2 μg mL −1 upon using Tween‐80 and or CMC, respectively. The method was successfully applied to the analysis of ETC in its pharmaceutical formulations (either alone or in presence of other co‐formulated drugs). The results were in good agreement with those obtained using the official method. The methods were further extended to determine the drug in human plasma samples, and to study the pharmacokinetics of ETC . The paper is the first report on the spectrofluorimetric determination of entacapone.